Pengaruh Kepemimpinan Transformasional terhadap Kinerja Perusahaan pada PT Pos Indonesia (Persero): Peran Mediasi Keberlanjutan Perusahaan - Junengsih; Basori, Mohamat; Intan, Lusi Reni (CV ODIS, 2025)
Abstract. This study aims to examine the influence of transformational leadership on company performance by incorporating corporate sustainability as a mediating variable. The research is centered on PT Pos Indonesia (Persero), a state-owned enterprise striving to improve competitiveness and performance through organizational and digital transformation. A quantitative explanatory research design was adopted. Data were collected from 316 permanent employees across various organizational units using a structured questionnaire. The analysis employed Structural Equation Modeling using the Partial Least Squares (SEM- PLS) method with SmartPLS version 3.0. The results reveal that transformational leadership has a significant positive effect on both corporate sustainability and company performance, directly and indirectly. Corporate sustainability significantly mediates the relationship between transformational leadership and performance, indicating that visionary and inspirational leaders foster sustainable systems that enhance organizational outcomes. These findings underscore the strategic synergy between modern leadership styles and sustainability practices in achieving superior and enduring corporate performance